Narrative and orality. A case study - Morillas, Esther (MonTi Monografías de Traducción e Interpretación, 2018)
Orality used as a discursive strategy in written texts is nothing new. However, it could be said to be one of the most promoted strategies in contemporary literary production. Through the analysis of Marco Malvaldi’s novel La briscola in cinque and its translation into Spanish, by Juan Carlos Gentile Vitale, I will illustrate the process through which the elements that characterize orality (at least, conventionally) are translated from one language to another. Dialogism will be especially relevant to this study, as well as its expressivity, the role of dialect and its relationship with humor.